Rerupture outcome of conservative versus open repair versus minimally invasive repair of acute Achilles tendon ruptures: A systematic review and meta-analysis. - Haidong Deng; Xin Cheng; Yi Yang; Fang Fang; Jialing He; Yixin Tian; Tiangui Li; Yangchun Xiao; Yuning Feng; Peng Wang; Weelic Chong; Yang Hai; et al. (PLoS ONE)
Objective To compare the rerupture rate after conservative treatment, open repair, and minimally invasive surgery management of acute Achilles tendon ruptures. Design Systematic review and network meta-analysis. Data sources We searched Medline, Embase, and the Cochrane Central Register of Controlled Trials from inception to August 2022. Methods Randomised controlled trials involving different treatments for Achilles tendon rupture were included. The primary outcome was rerupture. Bayesian network meta-analysis with random effects was used to assess pooled relative risks (RRs) and 95% confidence intervals. We evaluated the heterogeneity and publication bias. Results Thirteen trials with 1465 patients were included. In direct comparison, there was no difference between open repair and minimally invasive surgery for rerupture rate (RR, 0.72, 95% CI 0.10-4.4; I2 = 0%; Table 2). Compared to the conservative treatment, the RR was 0.27 (95% CI 0.10-0.62, I2 = 0%) for open repair and 0.14 (95% CI 0.01-0.88, I2 = 0%) for minimally invasive surgery. The network meta-analysis had obtained the similar results as the direct comparison. Conclusion Both open repair and minimally invasive surgery were associated with a significant reduction in rerupture rate compared with conservative management, but no difference in rerupture rate was found comparing open repair and minimally invasive surgery.